KEABSAHAN PERJANJIAN KREDIT BANK DAN TANGGUNG JAWAB HUKUM ATAS PEMBERIAN HAK TANGGUNGAN OLEH PIHAK YANG TIDAK BERWENANG - Niru Anita Sinaga (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN, 2025)
A banking credit agreement is a principal contract that forms the legal basis for the relationship between the bank as the creditor and the customer as the debtor. In banking practice, to ensure the fulfillment of the debtor’s legal obligations, banks require collateral in the form of a Mortgage Right (Hak Tanggungan), which is regulated under Law Number 4 of 1996 concerning Mortgage Rights. The Mortgage Right is accessory to the banking credit agreement and is only legally valid if granted by a party legally authorized in their capacity as the holder of rights over the mortgaged object. However, in practice, there are often cases where the Mortgage Right is granted by an unauthorized party due to lack of ownership, legal incapacity, or failure to obtain the required consent from other parties as mandated by applicable laws and regulations. This issue raises legal implications regarding the validity of the Mortgage Right, the validity of the banking credit agreement as the principal contract, and the legal responsibilities of the parties involved. This study aims to analyze the validity of banking credit agreements when the Mortgage Right is granted without meeting the legal requirements and to examine the resulting legal responsibilities. Using normative legal research supported by statutory and conceptual approaches, the study finds that Mortgage Rights granted by unauthorized parties are legally invalid and therefore do not provide effective legal protection for the bank, without automatically nullifying the banking credit agreement except under certain conditions. These findings underscore the importance of prudence and good faith by banks and related parties in banking operations.